Brief Study on the Decomposition of Tetraethylene Glycol Dimethyl Ether (Tegdme) Solvent in the Presence of Li2o2 and H2o2 - Aguirre-Quintana, M; Aguirre-Quintana, M; Herrera-Diaz, F; Herrera-Diaz, F; Márquez-Mandiola, P; Márquez-Mandiola, P (Sociedad Chilena de Quimica, 2021)
In this work, the decomposition of the solvent tetraethylene glycol dimethyl ether (TEGDME) was studied under conditions that simulate the charge of a Li-O2 cell in the presence and absence of hydrogen peroxide and lithium peroxide by means of electron spin resonance spectroscopy (ESR). We detected the formation of radical species, although in low concentrations, originating from solvent decomposition reactions during the oxidation process, in the absence of peroxides. On the other hand, by introducing H2O2 and H2O into the system, oxygen-centered superoxide and hydroxyl radical species were detected. Furthermore, in the presence of Li-O2, carbon-centered radical species were detected which clearly show the decomposition of the solvent. Finally, the results show that it is very important that the charging process of a Li-O2 cell is carried out by direct oxidation via 2 e- to Li2O2 to avoid the formation of radical species that the decomposition of the solvent. © 2021 Sociedad Chilena de Quimica. All rights reserved.